Influence of group sizes and food resources in home-range sizes of capybaras from Argentina - Corriale, Maria Jose (2013)
Within a species, home-range size can vary due to intrinsic and extrinsic factors. In this study we test the hypotheses that social group sizes (intrinsic) of capybaras (Hydrochoerus hydrochaeris) and food availability in their habitat (extrinsic) affect their home-range sizes. We used the minimum convex polygon method to estimate home-range sizes and core areas (the area in which each group was present during all seasons). Home-range size estimates varied from 11.3 ha to 27.6 ha (X̄ = 19 ha ± 1.89 SE). Core area accounted for a mean 22.5% of the total home-range size. Home ranges measured during autumn and winter were significantly larger than those recorded in spring and summer. The correlation between home-range size and mean number of adults in groups was marginally significant, whereas that between home-range size and the overall average group size was not significant. We observed a significant negative linear correlation between home-range size and estimators of food availability. The evidence that we determined does not allow us to establish any relationship between group size and home-range size, but it lends support to the hypothesis that the abundance of food resources is a major limiting factor in determining home-range size.